Gamification as a cultural tourism marketing strategy for generation z - Ulfa, Nurul; Irfansyah (Jurnal Pariwisata Pesona, 2025)
Generation Z as 33% of Samarinda City's population. Represents significant opportunity for the development of digital-based cultural tourism, as highlighted by the East Kalimantan Tourism Office, which emphasizes the critical role of Gen Z in smart-tourism promotion and creative industries, particularly in the areas surrounding the Ibu Kota Negara (IKN). Gen Z's preference for visual, interactive, and tech savy experiences makes them a key target audience in tourism promotion strategies. This study aims to design an engaging cultural tourism experience for Generation Z using Augmented Reality (AR) technology and gamification. Employing the Double Diamond method with a qualitative approach, the process begins with needs exploration and progresses to prototype testing. The tourism concept “Bahari, Kini, Kena” was tested on ten Gen Z respondents in the form of an exploration of the Samarinda Seberang area, involving interactive activities such as quizzes, searching for hidden objects using AR, and introducing local culture, such as visiting the Shiratal Mustaqiem Mosque cultural heritage site, crossing the Mahakam River using traditional Tambangan boats, and tasting Ramadan-specific dishes like Peca' porridge. Tourism media included an AR app, a pocket guidebook, and interactive souvenirs. The pilot test results showed that amenities received the highest satisfaction score (4.8/5), followed by attractions and activities (4.6), accessibility (4.4), and technology (4.3). The main challenges included limitations in the app system and insufficient tourism infrastructure. This study concludes that an AR-based and gamification approach can enhance Gen Z's engagement in cultural tourism and serve as an effective strategy for promoting local destinations in a contextual, immersive, and sustainable manner.